Za pridobivanje novih znanj ni nikoli prepozno - Petkovšek Gregorin, Romana (Rehabilitacija (Ljubljana), 2020)
Background: Peripheral arterial disease is a key cause of amputations of the lower limb. Education of patients can widen their knowledge about the care for their feet. With knowledge and consistent care for the limb at risk, they can avoid potential problems that lead to limb amputation. The aim of our study was to determine whether there is a difference in knowledge about the care for the residual limb between patients with different causes of amputation and whether there is a difference in knowledge before and after the course. Methods: A longitudinal quantitative nonexperimental study was carried out using a questionnaire. It was conducted from January to December 2014. The study included 102 patients with unilateral lower limb amputation, regardless of the level of amputation (75 men and 28 women). The patients responded to the questions on Likert-type scales. The estimated internal consistency of the questionnaire was 0.88. Results: Bivariate analyses indicated that knowledge is statistically significantly associated with the following patients% characteristics: smoking (p = 0.027), diabetes (p = 0.024), previous instructions on leg care (p = 0.002), frequent feet screening (p = 0.050) and impairment of kidneys (p < 0.001). Multiple linear regression highlighted the frequency of leg scans as the only statistically significant independent factor associated with knowledge (p = 0.029). Comparison of knowledge before and after the education programme showed statistically significant improvement (p < 0.001). Conclusions: Our study showed that the patients gained knowledge that will be useful for them in maintaining the good condition of the remaining leg. At the end of the education programme, they had more knowledge that will help them in identifying risks and deciding on changing the behaviour that poses risk to their health.
Keywords: amputacija; izobraževanje; nega; rehabilitacija; zdravstvena nega; znanje